Effect of free nitrous acid on extracellular polymeric substances production and membrane fouling in a nitritation membrane bioreactor - Jiang, Yishuai (2023)
The membrane bioreactor (MBR) with nitritation based nitrogen removal processes has attracted growing interest in recent years, although membrane fouling in the nitritation MBR is a challenging issue. In this study, the inhibitory effect of free nitrous acid (FNA) on microbial extracellular polymeric substances (EPS) production and membrane fouling in a nitritation MBR was investigated. Results showed that EPS played a critical role in the biofouling process, and EPS production was affected by FNA concentration. As FNA concentration increased from 5.10 × 10-3 mg N/L to 1.34 × 10-2 mg N/L, protein (PN) and polysaccharide (PS) contents increased from 8.20 to 60.28 mg/g VSS and 4.74-30.46 mg/g VSS, respectively. However, when FNA concentration was 1.48 × 10-2 mg N/L, PN and PS reduced by 20.0% and 10.9%, respectively, indicating that the higher FNA concentration could reduce EPS production. The EPS reduction could be attributed to reduction in the loosely bound (LB) and tightly bound (TB) EPS but not the soluble microbial products (SMP). It was further revealed that higher FNA concentrations up to 1.48 × 10-2 mg N/L consequently mitigate trans-membrane pressure (TMP) rate in terms of dTMP/dt by 25.5% in the nitritation MBR. High throughput sequencing analysis revealed that the increase in FNA led to enrichment of Nitrosomonas but reduction in heterotrophic bacteria. This study showed that the appropriate FNA concentration affected EPS production and hence membrane fouling, leading to the possibility of membrane fouling mitigation by in-situ generated FNA in the nitritation MBR.